Studi Perbandingan Dinding Geser dan Bracing Tunggal Konsentris sebagai Pengaku pada Gedung Bertingkat Tinggi - Astuti, Pinta (Semesta Teknika, 2016)
All of high-rise buildings should have sufficient stiffness the structure Â will existed when earthquake occurred. The addition of shear wall structure and concentrically single bracing are alternative way to increase stiffness of the structure. This research is comparating the natural period of the structure with variation of stiffener structure between shear wall structure and concentrically single bracing by taking a case study at Mataram City Apartments and Condominium, Yogyakarta. The building consists of two towers and every tower consist of 18 stories. Analytical calculations in this research based on technical data field, quality of materials, and the results of structural analysis with numerical program. The calculation based on SNI 03-1726-2002, SNI 03-1726-2012, and the Uniform Building Code (UBC) 1997 Chapter 16 on Requirements Design Structure. Three modification of the shear wall layouts in this research are use to understanding about the effect of adding shear walls and concentrically single bracing to the natural period structure. Based on the calculation, the structure has adequate capacity to support the load with the natural period of 1.83 seconds. Maximum allowable vibration time by SNI 03-1726-2002 is 3.24 seconds, SNI 03-1726-2012 is 2,59 seconds, while the Uniform Building Code (UBC) is 1.68 seconds. So, the natural period requirement for this structure is 1.68 seconds. From all models, only the last model which have sufficient stiffness with natural period that 1.66 seconds for shear wall and 1.67 for concentrically single bracing stiffener.Â